Kaidah Pengembangan dan Penguatan Inkubator Dalam Usaha Kecil Menengah (UKM) - Mohammad Habibi (MAMEN: Jurnal Manajemen, 2022)
This research is a business Incubator rule as a demand from the global economy, which occurs because of a rapid and very significant change where government rules and policies to help Small and Medium Enterprises (SMEs) survive during the crisis must be really effective. SMEs run effectively, namely through the identification of transmission lines that have an impact on SMEs and crisis mitigation measures, with a business strengthening, economic activities in East Java will be good from a business perspective through incubators. This research method uses a qualitative data approach with a system of people from various circles and finds out information about SME incubators in East Java where the system is used with an interview model for incubators and surveys to respondents as well as various characteristics of SMEs in East Java. The results and discussion of business principles that must be carried out by SME incubators are: a) Business vision and goals, be responsible. b) Values ​​in the rules guide top-level executives according to organizational values. c) strength (strength) weakness (weakness) opportunities (opportunities) threats (threats) as a whole. This analysis belongs to the reinforcement rule, because it is possible to rely on its strength as an advantage. d) Tactics of efficiency work operational business principles. time and effort. e) resource allocation, structured, responsible f) measurement of business principles to track performance outputs, targets for launching rules and the role of the incubator. Keywords: incubator rules, strengthening, business development.